Analysis of the Application of Electronic Data Processing (Edp) in The Accounting Information System at the Tanjung Pura Regional General Hospital, Langkat Regency - Zulfarahmi, Zulfarahmi; Rokan, Mustafa Kamal; Harahap, Rahmat Daim (International Journal of Education, Information Technology, and Others, 2023)
This study aims to determine the application of electronic data processing in the accounting information system at Tanjung Pura Regional General Hospital, Langkat Regency. The data analysis method used is descriptive method that describes a reality found then analyze the data based on theories that are directly related to the discussion of the problem to then be drawn conclusions. From the research conducted can be drawn a conclusion that with the application of electronic data processing systems in the accounting information system in the Regional General Hospital (RSUD) Tanjung Pura Langkat Regency then the hospital can produce financial reports with more quickly, precisely and completely and the data saves time and costs. Meanwhile, the application of EDP when viewed from the internal control system is still not good because there are functions in the hospital that perform duplicate tasks. The results showed that the EDP system owned by the hospital was very good and in accordance with the demands of the times, but the complete computer facilities and the good accounting information system used were not supported by sufficiently skilled personnel and lack of understanding to apply the system used by the hospital. The hospital also uses good internal control to supervise the hospital application system. In defining a system, there are two groups of approaches to defining a system and from the explanation that the definition of a system is a unit consisting of various elements in accordance with procedures that are related and interact to achieve a goal.